2009
DOI: 10.1007/s00508-009-1184-9
|View full text |Cite
|
Sign up to set email alerts
|

Heart rate-corrected QT interval and QT dispersion in patients with pulmonary hypertension

Abstract: In women with pulmonary hypertension, mean QTc and QTcd are positively correlated to mean pulmonary arterial pressure and are significantly increased in patients with severe pulmonary hypertension.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
38
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(42 citation statements)
references
References 21 publications
(25 reference statements)
2
38
2
Order By: Relevance
“…The mPAP of our patients was lower than in the comparable group in Hong-Liang's study (patients with mild-to-moderate PH) and lower than in Rich's study. Rich's sample clearly had higher pulmonary vascular resistance than our sample, and Hong-Liang did not provide these data [23,24]. The shorter QTc interval in our patients may have been due to lower dilatation of the right ventricle.…”
Section: Discussioncontrasting
confidence: 51%
See 2 more Smart Citations
“…The mPAP of our patients was lower than in the comparable group in Hong-Liang's study (patients with mild-to-moderate PH) and lower than in Rich's study. Rich's sample clearly had higher pulmonary vascular resistance than our sample, and Hong-Liang did not provide these data [23,24]. The shorter QTc interval in our patients may have been due to lower dilatation of the right ventricle.…”
Section: Discussioncontrasting
confidence: 51%
“…The QTc interval was longer in patients with PH than in controls (Hong-Liang's study, severe PH: 428.6 ± 32.8 ms, mild to moderate PH: 423.1 ± 30.2 ms; controls: 411.1 ± 28.4 ms; criteria for mild to moderate PH: mPAP ≥ 25 mm Hg and < 60 mm Hg, criteria for severe PH: mPAP ≥ 60 mm Hg) [23]. In Rich's et al study [24], the QTc interval was 454.8 ± 29 ms in patients with PH compared with 429 ± 18 ms in controls.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Electrophysiological mechanisms by which atrial stretch leads to supraventricular arrhythmias are not fully understood, but studies suggest that volume and pressure overload in the heart can activate stretchactivated ion channels inducing atrial premature beats (NAZIR & LAB, 1996;KAMKIN et al, 1999). Another risk factor for the arrhythmogenic substrate in the dog of the present report is the presence of pulmonary hypertension, which can modulate autonomic activity and delay cardiac repolarization (HONG-LIANG et al, 2009;RAJDEV et al, 2012).…”
mentioning
confidence: 70%
“…Arrhythmogenic substrate in rat hearts with monocrotaline-induced pulmonary hypertension may cause steeper RV electrical restitution and rate-dependent RV-LV action potential duration-dispersion, 4 inducing ventricular tachycardia and fibrillation. A study of 201 pulmonary hypertension patients 5 demonstrated that mean heart-rate corrected QT interval (QTc) and QTc dispersion (QTcd) were significantly increased in severely ill patients, compared to patients with mild to moderate pulmonary hypertension. In addition, in women these indices were positively correlated to mean pulmonary arterial pressure, identifying a possible substrate for ventricular arrhythmias.…”
Section: Plausible Causes Of Arrhythmiamentioning
confidence: 99%